Fundamentals of performance improvement optimizing results through people, process, and organizations : interventions, performance support tools, case studes - Van Tiem, Darlene M. (Pfeiffer, 2012)
"Fundamentals of Performance Improvement is a practical how-to guide designed to help practitioners and students understand the science of performance technology and successfully implement organizational change. Using the Human Performance Technology (HTP) model, the authors explain step-by-step how to spot performance indicators, analyze problems, identify their underlying causes, and create workable solutions, and perspective on change management. The completely updated and revised third edition will also feature expanded sections on intervention design and development, tips for sustaining change over time, and all new case studies contributed by top practitioners and academics in the field"--